Natal tooth: A Case Report and Review - Peedikayil, F; Prabhakaran, P (Journal of Nepal Paediatric Society, 2011)
Natal teeth are defined as teeth that are present in the mouth at the time of birth. It must be considered that natal and neonatal teeth are conditions of fundamental importance not only for a dental surgeon but also for a paediatrician, since their presence may lead to numerous complications. Hence the purpose of the present paper is to review and discuss its clinical features, complications and management. Key words: Natal teeth; neonatal tooth; congenital teeth; foetal teeth; pre-deciduous teeth; premature teeth; dentitia praecox DOI: http://dx.doi.org/10.3126/jnps.v31i3.4997 J Nep Paedtr Soc 2011;31(3): 251-253